Visit(s) to the Museum: Visitors and Official Information Available on the Web - Sousa, O.; Oliveira, A. (A Digital Janus: Looking Forward, Looking Back, 2014)
The affirmation of the ‘net society and the growing importance of the Internet has changed the reality of museums. The introduction of the provision of information as a function, affected the traditional functions of the museums, and the museological experience also changed. The development of websites and use of Web 2.0 instruments has proved to be fundamental to the process of integration, providing context and complementing the information provided by the museum, allowing the user to participate actively. By providing complementary and contextual information, communicated by the museum itself, and allowing the interaction with users, websites and Web 2.0 tools contribute to the relation traditionally developed between the museum and its users, namely to the formation of opinions. This study included four Portuguese museums and their Web tools. A questionnaire was developed to understand how museum visitors use the official information available on the Web to form an opinion about the services the museum provides. The data was processed statistically and the findings revealed a low use of and participation in the Web resources by museum users, establishing a low connection with the visit. These results contribute to a new way of analysing the relations between the visitors, Web resources and the museums, in Portugal, and expose the necessity of new approaches to the subject.